Middle-management support and safety training from towards employees safety behavior in the manufacturing environment - Marzlan, Othman (2013)
Safety behavior among workers at workplace is the important in leading towards safety compliance and safety indicators at any organization. In this research study, the variables influence the safety behavior at workplace had been explored and analyzed. There are three independent variables are identified, they are demographic factor, middle-management support and safety training program and one dependent variable for this project paper which is safety behavior among employees at workplace. Total of 163 sample size has been taken from various level groups that consist of middle management such as engineers and shift managers also lower level employees such as technicians, trainers and manufacturing specialist. Study survey has been conducted through random sampling. A total of 200 questionnaires had been distributed to the sample of choose on the study consist of three independent variables of employee safety behavior that are: a) middle management support, b) safety training program and c) demographic. Quantitative survey has been used for this study. From regression analysis result shows that two (2) hypotheses supported with significant value less than 0.05 significant levels. The result concludes that middle-management support did not give a significant impact to the safety behavior among employees at workplace. However, the result concludes that safety training program did give a significant impact to the safety behavior among employees at workplace. The finding of the study had proven that employee safety behavior is influenced by safety training programs held at workplace. In hypothesis two, the researcher found, the employee safety behavior will not increase with the support and commitment given by the middle level management. Researcher had also revealed that the safety training program had a positive relation with the middle management support. Therefore safety of employees is primary important at workplace